Optical and morphological properties of soot particles generated by the miniCAST 5201 BC generator. Issue 7 (2nd June 2021) - Ess, Michaela N.; Bertò, Michele; Irwin, Martin; Modini, Robin L.; Gysel-Beer, Martin; Vasilatou, Konstantina
Abstract: The miniCAST 5201 black carbon (BC) generator is a novel soot generator able to produce soot particles with a wide range of properties in a stable and reproducible manner. In this study, particles generated with diffusion and premixed flames were comprehensively analyzed, with a special focus on particle morphology, nanostructure, and optical properties. It was found that aggregate BC particles with a mean electrical mobility diameter of about 160 nm generated with an overall near-stoichiometric diffusion flame consist of primary particles with turbostratic layers and onion-like structures. Moreover, they possessed an absorption Ångström exponent (AAE) close to 1, low single scattering albedo (SSA), and a mass absorption cross-section MAC870nm, total (calculated from photoacoustic absorption coefficient and total particle mass) of 4.3 m 2 /g. With premixed flames under fuel-lean conditions, particles with mean mobility diameters of 50 nm, 75 nm, and 100 nm could be generated with high elemental carbon to total carbon mass fractions (>85%). These particles had a high structural order, exhibited an AAE of 1.1–1.2, low SSA and MAC870nm, total of 3.0–3.3 m 2 /g. The similarities of the properties of the miniCAST generated soot particles to real-world engine-emitted soot particles indicate that the miniCAST 5201 BC generator is a very promising source of reference aerosols for the calibration of BC diagnostic instruments and engine-exhaust particle counters.